2018
DOI: 10.1016/j.cels.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Time Sharing through Dynamic Pulsing in Single Cells

Abstract: SUMMARY In cells, specific regulators often compete for limited amounts of a core enzymatic resource. It is typically assumed that competition leads to partitioning of core enzyme molecules among regulators at constant levels. Alternatively, however, different regulatory species could time share, or take turns utilizing, the core resource. Using quantitative time-lapse microscopy, we analyzed sigma factor activity dynamics, and their competition for RNA polymerase, in individual Bacillus subtilis cells under e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 59 publications
3
48
1
Order By: Relevance
“…Additionally, we found that correlations between the sigma factor regulons largely agreed with the concept of molecular time sharing, i.e. the idea that sigma factors compete for RNA polymerases (Figure S7) (22).…”
Section: Microsplit Generates High-quality Single-cell Rna-seq Datasupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, we found that correlations between the sigma factor regulons largely agreed with the concept of molecular time sharing, i.e. the idea that sigma factors compete for RNA polymerases (Figure S7) (22).…”
Section: Microsplit Generates High-quality Single-cell Rna-seq Datasupporting
confidence: 74%
“…To obtain an even finer-grained picture of the transcriptional programs during exponential growth and entry to stationary phase, we inferred the activity profiles of select transcriptional regulators (TR) from expression of the genes in their respective regulons (Figure 2D and S8) (22). This analysis revealed pronounced changes in regulation of carbon utilization, stress responses, metal uptake, developmental decisions and more.…”
Section: Microsplit Generates High-quality Single-cell Rna-seq Datamentioning
confidence: 99%
“…The EMBO Journal 38: e101876 | 2019 associated with transient fitness gain (Smits et al, 2006;Veening et al, 2008). For instance, in Bacillus subtilis alternative sigma factors are expressed in pulses (Park et al, 2018), likewise the tumor suppressor p53 in eukaryotic cells (Lahav et al, 2004). In E. coli, the DNA repair methyltransferase Ada is heterogeneously expressed in stress-free populations, also conferring discrete responsiveness to alkylating agents (Uphoff et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression can be noisy 1,2 , as can the growth of single cells 3,4 . Such cell-to-cell variation has been implicated in survival strategies for bacterial populations 57 .…”
mentioning
confidence: 99%
“…3d, 4b). However, the ΔrpoS strain also had a wide growth rate distribution suggesting growth rate is intrinsically heterogeneous 3 (Fig. 2e).…”
mentioning
confidence: 99%